2014
DOI: 10.1186/s13075-014-0479-z
|View full text |Cite
|
Sign up to set email alerts
|

Systemic pentraxin-3 levels reflect vascular enhancement and progression in Takayasu arteritis

Abstract: IntroductionProgression of arterial involvement is often observed in patients with Takayasu arteritis (TA) thought to be in remission. This reflects the failure of currently used biomarkers and activity criteria to detect smouldering inflammation occurring within arterial wall. Pentraxin-3 (PTX3) is a soluble pattern recognition receptor produced at sites of inflammation and could reveal systemic as well as localized inflammatory processes. We verified whether the blood concentrations of PTX3 and of C-reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 43 publications
5
52
1
2
Order By: Relevance
“…209,210 Of interest, patients with large vessel vasculitis are often treated with anti-cytokine agents targeting in particular TNFα and IL-6. PTX3 identified vascular progression only in patients who were not being treated with anti-TNFα agents, 208 in good agreement with the role of the cytokine as a major stimulus driving PTX3 expression in vivo (see above).…”
Section: Clinical Translation As a Biomarker Of Tissue And Vascularsupporting
confidence: 79%
See 1 more Smart Citation
“…209,210 Of interest, patients with large vessel vasculitis are often treated with anti-cytokine agents targeting in particular TNFα and IL-6. PTX3 identified vascular progression only in patients who were not being treated with anti-TNFα agents, 208 in good agreement with the role of the cytokine as a major stimulus driving PTX3 expression in vivo (see above).…”
Section: Clinical Translation As a Biomarker Of Tissue And Vascularsupporting
confidence: 79%
“…However, it appears increasingly clear that elevated levels identify subgroups of patients, such as those undergoing ischemic complications that represent the evolution of vacular lumen occlusion, such as optic neuritis in Giant Cell Arteritis 207 or progression of the vascular involvement because of unrestrained mural remodeling in Takayasu Arteritis. 208 The availability of novel, more refined non-invasive imaging approaches will be instrumental for a better stratification of patients with large vessel vasculitis in homogenous groups. 209,210 Of interest, patients with large vessel vasculitis are often treated with anti-cytokine agents targeting in particular TNFα and IL-6.…”
Section: Clinical Translation As a Biomarker Of Tissue And Vascularmentioning
confidence: 99%
“…Thus, it could provide a safe, non‐invasive means of assessing changes in vascular anatomy over time. It is still a matter of debate whether MRI can add useful information to disease activity assessment with a cross‐sectional, single time‐point assessment of arterial wall edema or post‐contrast enhancement …”
Section: Radiologymentioning
confidence: 99%
“…Hollan et al 40 reported that circulating PTX3 could likely be used as a biomarker for severity of CVD in inflammatory rheumatic disease. Tombetti et al 41 reported increased PTX3 concentration in SLE and Takayasu arteritis and might represent a biomarker of actual arteritis. Consistent with our results Shimada et al 42 reported increased PTX3 concentrations in SLE patients that was significantly associated with disease activity, however a significant correlation between PTX3 concentrations and carotid atherosclerosis was not found.…”
Section: Discussionmentioning
confidence: 98%